2013
DOI: 10.1177/1362361313495717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive transcranial magnetic stimulation in performing eye–hand integration tasks: Four preliminary studies with children showing low-functioning autism

Abstract: This report, based on four studies with children with low-functioning autism, aimed at evaluating the effects of repetitive transcranial magnetic stimulation delivered on the left and right premotor cortices on eye-hand integration tasks; defining the long-lasting effects of high-frequency repetitive transcranial magnetic stimulation; and investigating the real efficacy of high-frequency repetitive transcranial magnetic stimulation by comparing three kinds of treatments (high-frequency repetitive transcranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…The mild adverse events were as follows: headache (n=45) 15, 21, 64, 69-71, 75, 78 , dizziness (n=8) 66, 69, 70 , jaw twitching (n=4) 66 , nausea/vomiting (n=4) 21, 75 , anxiety (n=3) 69 , neck stiffness (n=3) 21 , tingling/dullness (n=3) 69, 75 , scalp pain (n=2) 13, 67 , neck pain (n=2) 70 , restlessness (n=1) 77 , and sleepiness (n=1) 14 . Moderate adverse events include generalized tonic-clonic seizure (n=3) 65, 68, 72 and rapid moodswings (n=1) 77 . The only severe adverse event to occur in rTMS stimulation is 8-9 hours of stimulation-induced hypomania (n=1) 72 .…”
Section: Resultsmentioning
confidence: 99%
“…The mild adverse events were as follows: headache (n=45) 15, 21, 64, 69-71, 75, 78 , dizziness (n=8) 66, 69, 70 , jaw twitching (n=4) 66 , nausea/vomiting (n=4) 21, 75 , anxiety (n=3) 69 , neck stiffness (n=3) 21 , tingling/dullness (n=3) 69, 75 , scalp pain (n=2) 13, 67 , neck pain (n=2) 70 , restlessness (n=1) 77 , and sleepiness (n=1) 14 . Moderate adverse events include generalized tonic-clonic seizure (n=3) 65, 68, 72 and rapid moodswings (n=1) 77 . The only severe adverse event to occur in rTMS stimulation is 8-9 hours of stimulation-induced hypomania (n=1) 72 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study of high-frequency rTMS on the left premotor cortex showed a significant increase in eye-hand performances in autistic children [40]. In addition, naming improved after rTMS of the left pars triangularis as compared with sham stimulation was observed [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, HF-rTMS has also been used to increase excitability in inhibited cortical regions in children with ASD with intellectual disability. Investigators have reported significant improvement in eye-hand coordination, especially when behavioral training was paired with HF-rTMS (8 Hz, 90% rMT, 30 trains of 3.6 seconds, 3–10 sessions) applied to premotor cortex [79]. While these trials support plausible efficacy of rTMS in the relief of some ASD symptoms in children and adolescents, they are susceptible to placebo effects owing to their open-label nature.…”
Section: Tms Therapeutic Potentialmentioning
confidence: 99%